2015
DOI: 10.5348/ijhpd-2015-40-cr-15
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Her2/neu receptor in Carcinoma Gallbladder correlates significantly with advanced tumor stage

Abstract: Aims: Overexpression of Her2/neu is associated with increased disease recurrence and worse prognosis in many cancers. the aim of this study was to correlate Her2/neu positivity with the histopathological features in carcinoma gallbladder. Methods: this study was conducted on 54 cholecystectomy specimens of carcinoma gallbladder in a superspecialty referral center from January 2007 to July 2011. A gross evaluation of tumor, study of histopathology and immunohistochemical staining was done for Her2/neu. the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…13 Ashai et al studied the HER2/neu expression in correlation to advanced tumour stage of gall bladder carcinoma and showed that 46% cases were score 1+, 23% were score 2+, 9% cases were 3+ and 19% cases were negative. 14 We also evaluated HER-2/neu expression in gall bladder carcinoma and found similar results. Majority of cases (48%) have score 1+, while 20% and 24% cases have score zero and 2+.…”
Section: Discussionsupporting
confidence: 55%
“…13 Ashai et al studied the HER2/neu expression in correlation to advanced tumour stage of gall bladder carcinoma and showed that 46% cases were score 1+, 23% were score 2+, 9% cases were 3+ and 19% cases were negative. 14 We also evaluated HER-2/neu expression in gall bladder carcinoma and found similar results. Majority of cases (48%) have score 1+, while 20% and 24% cases have score zero and 2+.…”
Section: Discussionsupporting
confidence: 55%
“…In patients with advanced breast and gastric cancer, Her-2 receptor blockers (Trastuzumab) have already been incorporated into conventional chemotherapy with good results. In gallbladder cancer, there have been reports regarding the overexpression and amplification of Her-2 (15,16,17). Scoring protocols for Her-2 expression in breast and gastric carcinomas are standardized, however, not for carcinomas arising in other body organs like the gallbladder.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have been done worldwide about overexpression of the Her-2 gene in gallbladder carcinoma (14)(15)(16)(17) but have never been performed in our country even though Pakistan has a high incidence of gallbladder cancer. This study was conducted in our population to determine the over-expression of Her-2 in gallbladder adenocarcinoma to determine the subset of patients who can get benefit from anti-Her-2 therapy.…”
Section: Introductionmentioning
confidence: 99%